Digital and Analog Detection of SARS-CoV-2 Nucleocapsid Protein via an Upconversion-Linked Immunosorbent Assay - Brandmeier, Julian C; Jurga, Natalia; Grzyb, Tomasz; Hlaváček, Antonín; Obořilová, Radka; Skládal, Petr; Farka, Zdeněk; Gorris, Hans H (Analytical chemistry, 2023)
The COVID-19 crisis requires fast and highly sensitive tests for the early stage detection of the SARS-CoV-2 virus. For detecting the nucleocapsid protein (N protein), the most abundant viral antigen, we have employed upconversion nanoparticles that emit short-wavelength light under near-infrared excitation (976 nm). The anti-Stokes emission avoids autofluorescence and light scattering and thus enables measurements without optical background interference. The sandwich upconversion-linked immunosorbent assay (ULISA) can be operated both in a conventional analog mode and in a digital mode based on counting individual immune complexes. We have investigated how different antibody combinations affect the detection of the wildtype N protein and the detection of SARS-CoV-2 (alpha variant) in lysed culture fluid via the N protein. The ULISA yielded a limit of detection (LOD) of 1.3 pg/mL (27 fM) for N protein detection independent of the analog or digital readout, which is approximately 3 orders of magnitude more sensitive than conventional enzyme-linked immunosorbent assays or commercial lateral flow assays for home testing. In the case of SARS-CoV-2, the digital ULISA additionally improved the LOD by a factor of 10 compared to the analog readout.
Keywords: ELISA; senzitivita a specificita; Antibodies, Viral; imunosorbenty; Nucleocapsid Proteins; Enzyme-Linked Immunosorbent Assay; lidé; protilátky virové; Sensitivity and Specificity; Immunosorbents; Humans; nukleokapsida - proteiny; COVID-19; SARS-CoV-2